Characterizing Electrocochleography in Cochlear Implant Recipients with Residual Low-Frequency Hearing - Bester, Christofer W.; Campbell, Luke; Dragovic, Adrian; Collins, Aaron; O'Leary, Stephen J. (Frontiers in Neuroscience, 2017)
Objective: Lay the groundwork for using electrocochleography (ECochG) as a measure of cochlear health, by characterising typical patterns of the ECochG response observed across the electrode array in cochlear implant recipients with residual hearing. Methods: ECochG was measured immediately after electrode insertion in 45 cochlear implant recipients with residual hearing. The Cochlear Response Telemetry system was used to record ECochG across the electrode array, in response to 100- or 110-dB SPL pure tones at 0.5-kHz, presented at 14 per second and with alternating polarities. Hair cell activity, as the cochlear microphonic (CM), was estimated by taking the difference (DIF) of the two polarities. Neural activity, as the auditory nerve neurophonic (ANN), was estimated by taking the sum (SUM) of the two polarities. Prior work in humans and animal studies suggested that the expected ECochG pattern in response to a 0.5-kHz pure tone is an apical-peak in CM amplitude and latency. Results: The most prevalent pattern was a peak in the DIF amplitude near the most apical electrode, with a prolongation of latency towards the electrode tip; this was found in 21 / 39 individuals with successful ECochG recordings. The 21 apical-peak recipients had the best low-frequency hearing. A low amplitude, long-latency DIF response that remained relatively constant across the electrode array was found in 10 / 39 individuals, in a group with the poorest low- and high-frequency hearing. A third, previously undescribed, pattern occurred in 8 / 39 participants, with mid-electrode peaks in DIF amplitude. These recipients had the best high-frequency hearing and a progressive prolongation of DIF latency around the mid-electrode peaks consistent with the presence of discrete populations of hair cells. Conclusions: The presence of distinct patterns of the ECochG response with relationships to pre-operative hearing levels supports the notion that ECochG across the electrode array functions as a measure of cochlear health.